2010
DOI: 10.1175/2010mwr3023.1
|View full text |Cite
|
Sign up to set email alerts
|

Initial Maintenance of Tropical Cyclone Size in the Western North Pacific

Abstract: A tropical cyclone (TC) size parameter, which is defined here as the radius of 15 m s 21 near-surface wind speed (R15), is calculated for 145 TCs in the western North Pacific during 2000-05 based on QuikSCAT oceanic winds. For the 73 TCs that intensified to typhoon intensity during their lifetimes, the 33% and 67% respective percentiles of R15 at tropical storm intensity and at typhoon intensity are used to categorize small, medium, and large TCs. Whereas many of the small TCs form from an easterly wave synopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 41 publications
5
70
1
Order By: Relevance
“…The mean TC size peaks in October, whereas the number of TCs peaks in August. The result is consistent with the findings of Brand (1972), Merrill (1984), Liu and Chan (1999), and Lee et al (2010), who found a maximum mean TC size in October in the western North Pacific.…”
Section: October 2013 S a T A K E E T A Lsupporting
confidence: 92%
See 1 more Smart Citation
“…The mean TC size peaks in October, whereas the number of TCs peaks in August. The result is consistent with the findings of Brand (1972), Merrill (1984), Liu and Chan (1999), and Lee et al (2010), who found a maximum mean TC size in October in the western North Pacific.…”
Section: October 2013 S a T A K E E T A Lsupporting
confidence: 92%
“…TCs are also characterized by their size, their extratropical transition timing (if any), and their meridional heat transport. The size of TCs has been approximately measured from observation data in a number of studies (Kimball and Mulekar 2004;Lee et al 2010;Merrill 1984). Sinclair (1997) and Rudeva and Gulev (2007) developed a method for finding the zero contours in the downgradient direction from the cyclone center and applied this technique to extratropical cyclones in the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…A large TC can also form near the center of the monsoon gyre (Lander 1994;Wu et al 2013), which suggests that the monsoon gyre is an important feature in determining TC size in the WNP. Similar results for WNP TCs using QuikSCAT and the US National Centers for Environmental Prediction (NCEP) Reanalysis 2 data were also obtained by Lee et al (2010). They further concluded that a TC generally maintains its size (R15) during intensification.…”
Section: Synoptic-scale Flow Associated With Small and Large Tcssupporting
confidence: 64%
“…Instead of using the winds at a given radius, they utilized the winds to calculate the relative vorticity, and then defined size as the radius at which the azimuthally-averaged relative vorticity decreases to 1 × 10 −5 s −1 (RRV) from the TC center. With the launch in 1999 of the QuikSCAT satellite, which has a wider swath and higher horizontal resolution (with a ~ 1800-km swath and a 12.5-km grid resolution), Lee et al (2010) used six years of this dataset to investigate TC size, which they defined as R15. Making use of the entire QuikSCAT dataset (1999 -2009), Chan and Chan (2012) used R17 as the definition of TC size to establish the climatology of TC size for the WNP and NA.…”
Section: Metrics Representing the Outer-core Wind Structure Of Tcsmentioning
confidence: 99%
“…For example, the size of a TC is potentially affected by the synoptic patterns associated with the dominant subtropical high (Liu and Chan, 2002;Chan and Chan, 2012). Lee et al (2010) found that small TCs are more influenced by the WNPSH during their intensification due to the increased environmental average wind speed in the north of the TC caused by a tighter pressure gradient between the cyclone and the subtropical high. On the interdecadal timescale, a weakening in vertical wind shear, or eastward retreating of the WNPSH, sets up favorable environments for more TC formations in the Philippine Sea (e.g., Lander, 1994;Harr and Elsberry, 1995;Chan, 2000;Chen and Chen, 2011).…”
Section: Shoujuan Shu Et Al: Environmental Influences On the Intensimentioning
confidence: 99%